成教云: $int(dx)/(e^(x)+e^(-x))=$()
举一反三
- 一阶非齐次线性微分方程 $y'=p(x)y+q(x)$ 的通解是( ). A: $\displaystyle y=e^{-\int p(x)dx}[\int q(x)e^{\int p(x)dx}dx+C]$ B: $\displaystyle y=e^{\int p(x)dx}[\int q(x)e^{\int p(x)dx}dx+C]$ C: $\displaystyle y=e^{\int p(x)dx}[\int q(x)e^{-\int p(x)dx}dx+C]$ D: $y=Ce^{-\int p(x)dx}$
- 若\( \int {f(x)dx = F(x) + C} \),则\( \int { { e^{ - x}}f({e^{ - x}})dx = } \)( ) A: \(- F({e^{-x}}) + C \) B: \( F({e^x}) + C \) C: \( F({e^{-x}}) + C \) D: \(- F({e^x}) + C \)
- 2.下列等式中,正确的是( ). A: $\int{{f}'(x)dx}=f(x)$ B: $\frac{d}{dx}\int{f(x)dx}=f(x)+C$ C: $\int{df(x)}=f(x)$ D: $d\int{f(x)dx}=f(x)dx$
- 若\( f(x) \)是\( g(x) \)的原函数,则( )。 A: \( \int {f(x)dx = g(x) + C} \) B: \( \int {g(x)dx = f(x) + C} \) C: \( \int {g'(x)dx = f(x) + C} \) D: \( \int {f'(x)dx = g(x) + C} \)
- \( \int { { e^x}\sin {e^x}dx = } \)( ) A: \( \cos {e^x} + C \) B: \( - \cos {e^x} + C \) C: \( \arccos {e^x} + C \) D: \( - \arccos {e^x} + C \)